Reducing Telemetry Use Is Safe: A Retrospective Analysis of Rapid Response Team and Code Events After a Successful Intervention to Reduce Telemetry Use. (July 2019) - Xie, Lijia; Garg, Trit; Svec, David; Hom, Jason; Kaimal, Rajani; Ahuja, Neera; Barnes, James; Shieh, Lisa
Interventions guiding appropriate telemetry utilization have successfully reduced use at many hospitals, but few studies have examined their possible adverse outcomes. The authors conducted a successful intervention to reduce telemetry use in 2013 on a hospitalist service using educational modules, routine review, and financial incentives. The association of reduced telemetry use with the incidence of rapid response team (RRT) and code activations was assessed in a retrospective cohort study of 210 patients who experienced a total of 233 RRT and code events on the inpatient internal medicine services from January 2012 through March 2015 at a tertiary care center. The incidence of adverse events for the hospitalist service was not significantly different during the intervention and postintervention period as compared to the preintervention period. Reducing inappropriate telemetry use was not associated with an increase in the incidence rates of RRT and code events.